2022
DOI: 10.23910/1.2022.2787a
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Genetic Variability, Heritability, Correlation and Path Analysis in Chrysanthemum (Dendranthema grandiflora Tzvelev)

Abstract: The studies were conducted in the Division of Flower and Medicinal Crops, ICAR-Indian Institute of Horticultural Research, Bengaluru to evaluate twenty genotypes of chrysanthemum under naturally ventilated polyhouse during 2019–21. The experiments were laid out in CRD with three replications for growth and flowering traits to determine the variability, heritability, genotypic and phenotypic coefficient of variation, correlation and path coefficient among 9 quantitative traits. Results revealed that magnitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
2
2
0
Order By: Relevance
“…Thus, selecting based on these characteristics will enhance performance and improve the flower yield. These agree with the results of Veluru et al (2019) [27] in China and Bennurmath et al (2022) [6] in chrysanthemum.…”
Section: Path Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, selecting based on these characteristics will enhance performance and improve the flower yield. These agree with the results of Veluru et al (2019) [27] in China and Bennurmath et al (2022) [6] in chrysanthemum.…”
Section: Path Analysissupporting
confidence: 93%
“…Kumar et al (2019) [14] in Marigold stated that flower yield per hectare positively correlated with plant height, plant spread, dry weight of flower, number of flowers per plant, flower diameter and flower yield per plant. Bennurmath et al (2022) [6] observed similar results in chrysanthemum. At phenotypic level, flower yield trait exhibited significantly positive correlation with traits like number of spikes per plant (0.922), number of flowers per spike (0.869), spike length (0.847), shelf life (0.827), leaf area (0.824), total chlorophyll (0.831), 100 flower weight (0.623), plant height (0.778), primary branches per plant (0.593) and secondary branches per plant (0.537).…”
Section: Correlationmentioning
confidence: 59%
“…observed a positive correlation between ower size and other oral traits in diploid Roses. The same as our result positive signi cant correlation with days to owering, ower size, and some other oral traits was reported byKumar et al (2012). As picrocrocin and crocin belong to glycoside compounds and sugar is one of the main components of glycosides,(Tung et al 2022) the negative correlation between sugar and these two compounds in this study seemed reasonable thoroughly.…”
supporting
confidence: 92%
“…In this concern, Sainath et al, (2014) On chrysanthemum wreath L, Gupta et al (2015) On China aster, Bergmann et al ( 2016) On Euphorbia pulcherrima, Gad et al (2016) on Ixora coccinea. Gaurav, et al (2016) in Dendranthema grandiflora, Kudmate, et al (2016) on chrysanthemum plants, Mohamed (2017) on an aster plant (Symphyotrichum novi-belgii L.) and Bahmanyar (2020) on African marigold found that application of gibberellic acid at a concentration of 100 mg/L improved the vegetative and roots growth. El-Kinany et al ( 2019) on three Gaillardia cultivars, Thakur and Kumar (2020) in the Rosa damascena mill.…”
Section: Effect Of Planting Date Growth Stimulants and Their Combinat...mentioning
confidence: 99%